The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1002/em.2850230212
|View full text |Cite
|
Sign up to set email alerts
|

Studies on cytotoxic and genotoxic effects of cadmium nitrate and lead nitrate in chinese hamster ovary cells

Abstract: Cadmium nitrate decreased the viability of Chinese hamster ovary (CHO) cells in a concentration-dependent manner; 50% inhibition (IC50) was achieved at 0.015 mM. In contrast, lead nitrate appeared to be less toxic. Neither cadmium nitrate nor lead nitrate significantly increased frequencies of binucleated CHO cells with micronuclei (MN). However, both cadmium nitrate and lead nitrate could augment sister chromatid exchanges (SCEs). Cadmium nitrate induced SCEs with a potency approximately equal to that of mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 28 publications
1
9
0
3
Order By: Relevance
“…2). Although differences in the susceptibility of different cells [Lin et al, 1994] and of different organs [Valverde et al, 2002] to lead genotoxicity must be considered, the dose-response for micronuclei reported here in V79 cells coincides surprisingly well with the details of a recent study of micronuclei in the peripheral blood lymphocytes of workers occupationally exposed to lead [Vaglenov et al, 2001]. According to these authors, blood lead levels higher than 1.2 mM may pose an increased genetic risk.…”
Section: Discussionsupporting
confidence: 88%
“…2). Although differences in the susceptibility of different cells [Lin et al, 1994] and of different organs [Valverde et al, 2002] to lead genotoxicity must be considered, the dose-response for micronuclei reported here in V79 cells coincides surprisingly well with the details of a recent study of micronuclei in the peripheral blood lymphocytes of workers occupationally exposed to lead [Vaglenov et al, 2001]. According to these authors, blood lead levels higher than 1.2 mM may pose an increased genetic risk.…”
Section: Discussionsupporting
confidence: 88%
“…Lead exposure is also known to induce gene mutations and sister chromatid exchanges [201, 202], morphological transformations in cultured rodent cells [203], and to enhance anchorage independence in diploid human fibroblasts [204]. In vitro and in vivo studies indicated that lead compounds cause genetic damage through various indirect mechanisms that include inhibition of DNA synthesis and repair, oxidative damage, and interaction with DNA-binding proteins and tumor suppressor proteins.…”
Section: Leadmentioning
confidence: 99%
“…Furthermore, although Pb has been classified as a carcinogen by the World Health Organization [23], considerable differences in the genotoxic responses of organisms to Pb have been reported, including no genotoxic responses in some species. Increased sister-chromatid exchanges were detected in Chinese hamster ovary cells exposed to Pb in vivo [24]. Lead-induced chromosomal aberrations were also detected in cultured human leukocytes [25], but not in cultured Chinese hamster cells [26].…”
Section: Introductionmentioning
confidence: 92%